TELAAH ASAS GEEN STRAF ZONDER SCHULD TERHADAP PERTANGGUNGJAWABAN PIDANA PENIPUAN MELALUI MODUS RITUAL MISTIS - Ahda Muttaqin; Elmina A Herysta; Faisal Faisal; Pratama Putra Sadewa (UNIB Press, 2023)
Criminal act only refer to being prohibited and punishable by a criminal act. The principle of responsibility in criminal law is not to be punished if there is no mistake (Geen straf zonder schuld). This principle is not stated in written law but in unwritten law this principle applies. In the current era of globalization and technological developments, it does not immediately change the mindset of people to think rationally and modernly. But many Indonesian people without exception, educated or not, believe in mystical things. In crime, all parties can be subject to punishment, including in terms of assisting criminal acts. The purpose of this study is to formulate the norms of delict for fraud and to examine the geen straf zonder schuld principle of criminal liability for fraud through mystical rituals. The approach method used in this writing is a normative and statutory approach and a conceptual approach. The formulation of the problem in this paper is how to formulate the norms of delict delict through mystical rituals and how to study the geen straf zonder schuld principle of criminal liability for fraud. The conclusion of this study is that the formulation of the norm for delict acts of fraud lies in the ways and efforts that have been used by the perpetrators of the offense to move others to believe in something like mystical, supernatural things and the geen straf zonder schuld principle of criminal liability for fraud shows that the principle this is not stated in written law but in unwritten law this principle applies.